(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
This article explores the impact of the CoViD-19 pandemic, and the measures adopted in response to it, on women’s rights to health and reproductive health. It will argue that the pandemic has exacerbated systemic and deeply entrenched gender inequalities, and that it has been used as an excuse to restrict women’s rights to health and reproductive health through policies and laws whose declared purpose was to address the health emergency. It will provide examples of State practice in the field of access to abortion and maternal health and contend that States have legal obligations under international human rights law to guarantee access to these rights, also during emergencies.